Safety and efficacy of ultrasound-guided pigtail catheter insertion in pediatric intensive care unit: A single-center experience - Faiza Rahman; Abdul Rahim Ahmed; Anwarul Haque; Sadiq Mirza; Humaira Jurair (Journal of Pediatric Critical Care, 2020)
Objective: The study objective was to describe the safety and efficacy of ultrasound (US)-guided pigtail catheter (PC) (USGPC) placement at bedside for symptomatic pleural effusion and ascites in acute critically ill children in pediatric Intensive Care unit. and not critical care unit (PICU). Study Design: This was a descriptive study. Place: This study was conducted at the pediatric critical care unit (PICU) of The Indus Hospital, Karachi, Pakistan, from January 2018 to December 2019. Subjects and Methods: We retrospectively reviewed the electronic medical records of critically ill children who underwent USGPC insertion for symptomatic pleural effusions and ascites on bedside. Demographic data, clinical indication, success rate, and complications of procedures were collected using a structured questionnaire approved by the institutional ethical committee. The PC of 10–14 French size was placed under US guidance, using Seldinger technique by a pediatric intensivist team on bedside with procedural sedation and analgesia. Results: Forty patients (3.7% of the total admission) required PC insertion. The mean age of the patients was 8.3 years, and 55% (n = 22) were male. Nearly 85% (n = 34) of the patients had an underlying malignancy and presented as respiratory distress/failure secondary to either large pleural effusion and/or massive ascites. Indications were pleural effusions (n = 26, 65%) and ascites (n = 14, 35%). The procedure was successful in 92.5% of the patients. The mean duration of PC insertion was 13.9 days. Pneumothorax developed in three cases (7.5%) as a procedure-related complication, which resolved after chest tube insertion. None of the patients developed bleeding, or visceral injury. Resolution occurred in all cases. Conclusion: USGPC placement at bedside by intensivists for percutaneous drainage in symptomatic pleural effusion and ascites is a simple, safe, and an effective modality for critically ill children.